Manajemen Pembinaan Peserta Didik dalam Meningkatkan Disiplin dan Karakter di Sekolah - Azhar, Farid (Universitas Madako Tolitoli, 2024)
Student development management is a strategic process aimed at optimally directing, guiding, and developing students' potential, both in academic and non-academic aspects. Well-managed development not only produces high-achieving students but also students with noble character, positive character, and the ability to adapt socially in the environment outside the educational institution. This study aims to provide a comprehensive understanding of the urgency of implementing development management in educational institutions as an effort to create students with superior personalities and integrity. The method used is a literature study that reviews various scientific sources, such as journals, books, and educational regulations, relevant to the topic of student development. The results of the study indicate that development management plays an important role in forming positive attitudes towards the learning process, increasing discipline, and strengthening students' character in accordance with expected moral and ethical values. In addition, structured development has been proven to be able to create a conducive learning environment and increase student involvement in academic and non-academic activities. In conclusion, the implementation of effective development management is a key factor in realizing quality education. Therefore, educational institutions need to implement a planned, sustainable development strategy that is oriented towards developing students' character holistically.